Survey and Appraisal of the Salinity-Alkalinity Problem in Medium Irrigation Projects of Bhilwara District of Rajasthan - Ganu, S. N.; Moghe, V B; Shankaranarayana, H. S. (Journal of Soil and Water Conservation, 2022)
Rajasthan, which invariably co- under arid and semi-arid tract, us an acute shortage of water for rigated agriculture. Due to high linity in underground waters (Shan- arnarayana, etc al., 1963) and scar- ty of rainfall, the use of canal and ink water for irrigation in the state, receiving greater importance day day. At present nearly 16 lac lcres which comes to 45.7 0/ /o of the otal irrigated area, is under canal or tank irrigtion in whole of state.The canal irrigation, although in general, a boon in agricultural development, if not properly utilised have an adverse effect on the pro- perties of the soils of the area.